OPTIMALISASI ALAT MUAT ALAT ANGKUT SERTA ANALISIS BIAYA OPERASIONAL ORE GETTING DARI PIT KE STOCKPILE DI PT. FORMAT TEKNIK MANDIRI SITE SUBAIM KABUPATEN HALMAHERA TIMUR PROVINSI MALUKU UTARA - Gina Audina P Alhabsyi; Iyan Suryani; Ruth Bunga Ranggu; Andi Nurul isma (Journal Teknik Dan Teknologi, 2025)
PT. Format Teknik Mandiri is a private company operating in the mining sector which has a work contract in Subaim Village, Wasile Sub-district, East Halmahera Regency, North Maluku Province. Mining is carried out using an open mining system (Surface Mining) using the Open Cut Mining method, namely cutting from the ridge downwards. To create a mining activity that is sustainable, efficient and profitable, it is necessary to pay attention to every aspect that influences operational costs during mining. Controlling operating costs carried out regularly will make it easier for company management to control production costs for each mining/production activity so that expenses can be reduced to a minimum and can produce maximum profits. The aim of this research is to determine the production capabilities of mechanical equipment, analyze the costs that must be incurred by the company for ore getting activities. After conducting research, the author obtained a production volume of loading equipment of 3,844 m3 per day and production of transportation equipment for 3 Shacman F3000 units of 5,426 m3 per day with a total cost for 30 days (target time) the costs incurred were Rp. 738,061,200p.